AB0613 AUTONOMIC NEUROPATHY AND ITS PREDICTORS IN SYSTEMIC SCLEROSIS. (2nd June 2020) - Syngle, A.; Garg, N.; Gera, D.
Abstract : Background: Systemic sclerosis (SSc), a chronic autoimmune disease, is associated with autonomic neuropathy 1 . Autonomic neuropathy, especially cardiovascular autonomic neuropathy (CAN) is significant risk predictor of sudden cardiac death. However, its relationship with disease specific measures remains unexplored in SSc. Objectives: To assess cardiovascular autonomic neuropathy and sudomotor function and its predictors in systemic sclerosis. Methods: In this cross-sectional study, 16 SSc patients meeting the 2013 European League Against Rheumatism (EULAR) and American College of Rheumatology (ACR) classification criteria and 15 age and sex-matched healthy controls were recruited. Cardiovascular autonomic function assessed by five cardiovascular reflex tests according to Ewing. Peripheral sympathetic autonomic function assessed by FDA approved Sudoscan (Impeto Medical, Paris) through measurement of electrochemical skin conductance. Disease-specific measures (Disease duration, Modified Rodnan Skin Score (mRSS), EUSTAR activity score), and inflammatory measures (ESR, CRP) were determined. Quality of life measured by Scleroderma Health Assessment Questionnaire (SHAQ). Results: Systemic sclerosis patients had significantly impaired parasympathetic [Heart rate response to deep breath (HRD) (Fig. 1A ), Heart rate response to standing (HRS) (Fig. 1B ) and Heart rate response to valsalva manoeuvre (Fig. 1C )] and symapathetic [BP response to hand grip (BPH) (Fig. 1D )] function as compared to healthy controls. Scleroderma patients had significantly impaired sudomotor function (p<0.05) as compared to healthy controls. Levels of mRSS, EUSTAR score, ESR, CRP and SHAQ were significantly higher in SSc patients as compared to healthy controls (p≤0.05). Parasympathetic (HRD & HRS) dysfunction inversely correlated with ESR, CRP and mRSS. Sudomotor function positively correlated with mRSS, disease duration and CRP. Conclusion: CAN and Sudomotor function are significantly impaired in SSc. Parasympathetic dysfunction is more pronounced than sympathetic dysfunction in SSc. CAN and Sudomotor dysfunction are associated with disease-duration, skin-score, ESR and CRP. These could serve as potential predictors of Cardiovascular Autonomic neuropathy and sudomotor dysfunction in SSc. References: [1]Dessein PH, Joffe BI, Metz RM, Millar DL, Lawson M, Stanwix AE. Autonomic dysfunction in systemic sclerosis: sympathetic overactivity and instability. The American journal of medicine. 1992;93(2):143-50. Acknowledgments: None Disclosure of Interests: None declared